Effect of phosphodiesterase-5 inhibition on joint and muscle damage in rats with adjuvant arthritis - ERCAN, FERİHA; YÜKSEL, MERAL; ALİCAN, YAŞAR İNCİ (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2018)
Background/aim: This study was designed to examine the effect of tadalafil, a phosphodiesterase (PDE) 5 inhibitor, on the severity of joint and muscle damage in rats with adjuvant-induced arthritis (AA). Materials and methods: AA was induced by intradermal inoculation into right hind paw of male Sprague Dawley rats (300-450 g) with complete Freund's adjuvant (CFA; 0.1 mL). AA rats were treated with either tadalafil (10 mg/kg; per oral) alone or along with the soluble guanylyl cyclase inhibitor 1H-[1,2,4] oxadiazolo[4,3-a] quinoxalin-1-one (ODQ; 10 mg/kg; intraperitoneally). After decapitation on day 16, trunk blood was collected for total oxidant status (TOS) and total antioxidant capacity (TAC) assays. The left metatarsophalangeal joint and gastrocnemius muscle were excised for microscopic examination. Muscle samples were also evaluated in terms of malondialdehyde (MDA), glutathione, and chemiluminescence (CL) levels. Results: In tadalafil-treated AA rats, metatarsophalangeal joints revealed regular morphology of the cartilage with slight destruction and less inflammatory cell infiltration and vascularization in comparison to the controls (microscopic score: 1.17 +/- 0.31 vs. 4.17 +/- 0.79; P < 0.01). AA rats presented increased gastrocnemius muscle MDA, glutathione, and CL levels compared to the controls (P < 0.01, for MDA; P < 0.05, for glutathione; P < 0.05 for CL). Tadalafil attenuated the increase in CL levels (P < 0.01, for luminol and P < 0.001, for lucigenin). Serum TOS showed significant reductions by tadalafil. Conclusion: The long-acting PDE5 inhibitor tadalafil provides partial protection in a rat model of CFA-induced arthritis possibly via suppression of oxidant generation.
Keywords: Arthritis; phosphodiesterase-5; rat; tadalafil; PULMONARY ARTERIAL-HYPERTENSION; RHEUMATOID-ARTHRITIS; ISCHEMIA/REPERFUSION INJURY; SILDENAFIL CITRATE; NITRIC-OXIDE; ISCHEMIA-REPERFUSION; LIPID-PEROXIDATION; OXIDATIVE STRESS; TADALAFIL; GLUTATHIONE